Cajón de arena (2020)
I decided to write to you because I remembered that it is easier to talk to someone other than me. As you may know, lately it has been easy to feel how our time is surrounded by a delicate veil protecting things from happening. Thus, the most atrocious acts seem to be illusory. In opposition, I want to build something that gives time to a world with and without the veil. Therefore, I imagine spaces where the currency of actions can be perceived: the uncomfortable and the well-known, but also the soft and the unknown. A simulated place that appears with the power granted by the disappearance. For instance, imagine those green textiles that cover construction sites. Maybe that's it. Perhaps that's why lately I thought about jumping off the bridge, and when I finally did I realized that I didn't fall? Afterward, I came to write to you. To invite you to fall and no to fall. To tell you about that day on the bridge. The experiences that I had, have come disorderly but I will try to assemblage them here. The letters, for example, are dialogues and texts where I try to specify certain ideas by confronting and sharing them. Additionally, the drawings, are devices to prototype and imagine more freely. There are also constructions, I conceive them as material and immaterial arrangements to recognize and build space. Oh? and there are the actions, momentary interventions to define duration and rhythm of the phenomena; in the end, everything has been consigned in my memory, or some memory, a virtual space without dimension or weight. As you will notice, I don't want to tell you much more. I hope you can feel something like that: an intuition of how fragile facts are, or at least anything that I can't describe.